Prognostic impact of the expression of NCR1 and NCR3 NK cell receptors and PD-L1 on advanced non-small cell lung cancer - Fend, Laetitia (Oncoimmunology, 2016)
The putative contribution of natural killer (NK) cells to immunosurveillance in non-small cell lung cancer (NSCLC) has been an ongoing conundrum. Here, we used a readily standardizable quantitative real time polymerase chain reaction (qRT-PCR) to measure the expression of NK cell receptors in total peripheral blood mononuclear cells (PBMC) from healthy volunteers (HV), patients with gastrointestinal stromal tumors (GIST), neuroblastoma (NB), melanoma or NSCLC. We quantified NCR1 (which codes for NKp46) and NCR3 (which codes for NKp30), as well as that of three NCR3 splice variants (which give rise to immunostimulatory NKp30A and NKp30B, as well as to immunosuppressive NKp30C). NSCLC patients expressed lower levels of NCR1 than did HV. Remarkably, NCR3 was lower in NSCLC patients than in HV as well as in all other malignancies. Moreover, a discrete proportion of NSCLC patients exhibited a particular low ratio between NKp30B and NKp30C (ΔBC). In the overall cohort, low expression of NCR3 correlated with poor overall and progression-free survival (PFS). When patients were stratified according to the level of PD-L1 expression by NSCLC cells, within the PD-L1(high) category (>5% positive tumors), the sole parameter that affected prognosis was the expression of NCR1. However, in patients bearing tumors with negative PD-L1 expression on tumor or tumor-infiltrating stromal cells, the ΔBC(low) patients exhibited a dismal prognosis. Altogether, these results strongly suggest that NK cells mediate immunosurveillance against NSCLC and that measuring NK cell receptor expression by blood cells can yield useful biomarkers for patient stratification.